Adrenal function during long‐term ACTH therapy for patients with developmental and epileptic encephalopathy. Issue 1 (14th December 2021) - Ueda, Yuki; Fujishige, Shuta; Goto, Takeru; Kimura, Shuhei; Namatame, Noriko; Narugami, Masashi; Nakakubo, Sachiko; Nakajima, Midori; Egawa, Kiyoshi; Kaneko, Naoya; Nakayama, Kanako; Hishimura, Nozomi; et al.
Abstract: Some patients with developmental and epileptic encephalopathy (DEE) respond to adrenocorticotropic hormone (ACTH) therapy but relapse soon after. While long‐term ACTH therapy (LT‐ACTH) has been attempted for these patients, no previous studies have carefully assessed adrenal function during LT‐ACTH. We evaluated the effectiveness of LT‐ACTH, as well as adverse effects (AE), including their adrenal function in three DEE patients. Patients underwent a corticotropin‐releasing hormone (CRH) stimulation test during LT‐ACTH, and those with peak serum cortisol below 15 μg/dL were considered to be at high risk of adrenal insufficiency (AI). Two of three responded, and their life‐threatening seizures with postgeneralized electroencephalogram (EEG) suppression decreased. Although no individuals had serious AE, CRH stimulation test revealed relatively weak responses, without reaching normal cortisol peak level (18 μg/dL). Hydrocortisone replacement during stress was prepared in a case with lower cortisol peak than our cutoff level. LT‐ACTH could be a promising treatment option for cases of DEE that relapse soon after effective ACTH treatment. The longer duration and larger cumulative dosage in LT‐ACTH than in conventional ACTH could increase the relative risk of AI. Careful evaluation with pediatric endocrinologists, including hormonal stimulation tests, might be useful for continuing this treatment safely.